Effect of factors on permittivity of coconut shell waste-based composite for microwave application - K B, Mekha; Nurhafizah, Abu Talip Yusof; Sudhakar, Kumarasamy; Norazwina, Zainol; Mohamad Shaiful, Abdul Karim (International Congress of Chemistry and Environment, 2025)
The growing reliance on electronic devices necessitates the development of advanced sustainable dielectric materials. This research explores coconut shell waste-based composites as eco-friendly alternatives to conventional substrates, focusing on optimizing their dielectric properties in terms of permittivity value for microwave applications. The study employs a two-level factorial design (TLFD) for the fabrication process and a two-level factorial analysis (TLFA) to evaluate the effects of mesh size (particle size), stirring time, weight percentage, and curing conditions on the performance of the composite. The composites were fabricated by integrating sieved coconut shell particles with epoxy resin and hardener, followed by curing, and their dielectric properties were characterized using waveguide techniques in the microwave frequency range. Significant findings revealed that larger mesh sizes (1.18 mm), higher filler weight percentages (20%), and shorter stirring times (10 minutes) yielded superior permittivity, with the highest value of 3.9075 achieved under heating conditions. Additionally, the loss tangent was also evaluated, revealing its relationship with processing conditions. These results underscore the significance of processing variables in enhancing composite performance and highlight the potential of coconut shell waste-based composites as sustainable, high-performance materials for advanced electronic applications. This study introduces an innovative use of coconut shell waste in dielectric composites, offering a sustainable and potentially scalable alternative to conventional materials. Future research will focus on scaling the process, optimizing performance across broader frequency ranges, and exploring additional applications in electronic devices.